Empirical evaluation of circling interface with head-mounted mouse emulator users. - Ka, Hyun W.; Simpson, Richard C. (Disability & Rehabilitation: Assistive Technology, 2017)
Purpose:To evaluate the performance of the circling interface, which is an alternative interaction method for selecting and manipulating on-screen objects based on circling the target, rather than pointing and clicking. Method:We conducted empirical evaluations with actual head-mounted mouse emulator users from two different groups: individuals with spinal cord injury (SCI) and individuals with cerebral palsy (CP), comparing each group’s performance and satisfaction level on pointing tasks with the circling interface to performance on the same tasks when using dwell-clicking software. Results:Across all operations, for both subjects with SCI and with CP, the circling interface showed faster performance than the dwell-clicking interface. For the single-click operation, the circling interface showed slower performance than dwell selection, but for both double-click and drag-and-drop operations, the circling interface produced faster performance. Subjects with CP required much longer time to complete the tasks compared to subjects with SCI. If errors caused by circling on an area with no target and unintentional circling caused by jerky movements and an abnormally tiny circle are automatically corrected by the circling interface, their performance accuracy with the circling interface outperformed existing solutions without a steep learning curve. Conclusions:Circling interface can be used in conjunction with existing techniques and this kind of combined approach achieve more effective mouse use for some individuals with pointing problems. It is also expected to be useful for both computer access and augmentative communication software.Implications for RehabilitationA circling interface will improve clinical practice by providing an alternative pointing method that does not require physically activating mouse buttons and is more efficient than dwell-clicking.Being used in conjunction with existing techniques, some individuals who are head mouse users can achieve more effective mouse use.The Circling interface can also work with AAC devices.